CARTEIRAS DE INVESTIMENTOS UMA APLICAÇÃO A PARTIR DO MODELO ELTON-GRUBER - Nascimento, Sergio Luiz (2011)
In the contemporary moment, there is an intense movement of financial capital, either because of mergers and acquisitions of companies, is the natural expansion of capitalism itself, thus leading organizations to seek alternative financing at lower costs, when it considered rates interest charged by financial institutions. Concurrent with this, monetary authorities seek to reduce circumstantially interest rates that drive the economy in order to to attract new investment in production and still preserve those existing. So even paradoxical, the reduction in interest rates promulgated by the authorities, does not display the same reduction rate from those practiced by the market. This leads individuals, whether or not investment managers to seek alternative investments that provide monetary gains in excess of those which are based on rates set by monetary authorities. Combining the search for resources by organizations and the pursuit of higher monetary gains by investors, the stock market becomes a relevant alternative. In order to achieve the best results in this environment, no need to use templates and other tools that provide the best balance between risk and return given that every investor emits at least some risk aversion. Several instruments are available to perform these relationships, however, many of them not available to the investor on the condition of an individual. And by this point, the model developed by Edwin Elton and Martin Gruber appears as an alternative to any investor, whether by their construction, whether for its operation.